INTERFERENSI BAHASA INDONESIA DALAM TUTURAN SISWA KELAS VIII DI SMP NEGERI 82 MALUKU TENGAH - Rukmini Arfan; Wa mirna; Nanik Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Abstracts consist of only one paragraph with a maximum This study examines the phenomenon of Indonesian language interference in the speech of eighth-grade students at SMP Negeri 82 Maluku Tengah. The interference occurs due to the influence of the Banda dialect of Ambon Malay, which functions as the students’ mother tongue and is predominantly used in their daily communication. The objective of this research is to describe the forms of Indonesian language interference and to identify the factors contributing to its occurrence in students’ speech. This study employed a descriptive qualitative method. Data were collected through classroom observations, interviews with the Indonesian language teacher, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed 125 instances of Indonesian language interference identified from 68 student utterances.1) The forms of interference include: i) phonological interference (35 data), consisting of vowel deletion of /i/ (5 data), deletion of the phoneme /t/ (1 data), addition of the phoneme /g/ (2 data), deletion of the phoneme /r/ (2 data), reduction of the phoneme /k/ (1 data), deletion of the phoneme /h/ (6 data), reduction of the phoneme /g/ (4 data), deletion of the phoneme /a/ (1 data), change of vowel /u/ to /o/ (7 data), change of vowel /e/ to /a/ (3 data), change of vowel /i/ to /e/ (2 data), and deletion of the suffix -an (1 data); ii) morphological interference (9 data), including affixation interference (2 data), prefixation interference (4 data), and reduplication interference (3 data); and iii) syntactic interference (81 data), comprising word-level interference (55 data)—including adverbs (15 data), pronouns (22 data), verbs (2 data), nouns (7 data), and particles (9 data); phrase-level interference (16 data)—including noun phrases (4 data), adjective phrases (5 data), and verb phrases (7 data); and clause-level interference (10 data)—including independent clauses (6 data) and dependent clauses (4 data). 2) The main factors causing interference are the dominance of the mother tongue, habitual use